Gender mainstreaming in the urban space to promote inclusive cities - Kiara Rampaul; Hangwelani Magidimisha-Chipungu (The Journal for Transdisciplinary Research in Southern Africa, 2022)
The roles of urban spaces in promoting people’s social experiences and interactions, and access to green spaces, are critical for long-term community building. While gender balance occurs in the use of metropolitan spaces, the urban environment can still be considered as a mostly masculine sphere. Women are still marginalised and unsafe in urban spaces. Gender mainstreaming is used to plan and design a gender inclusive city, which includes all women in decision-making processes and helps to achieve the Sustainable Development Goal 11. The exclusion of women and girls from the urban planning process generates a knowledge gap, resulting in public spaces that exclude them. There is a clear planning gap: women are excluded from urban planning and design procedures. The research study developed from the urge to examine if gender mainstreaming is used in the design of urban spaces. Data for the study were gathered using qualitative method. Primary data was through interview while secondary data includes policy and research focus documents. The study revealed that women’s experience and understanding of urban spaces varied from men’s, and that these differences must be considered when planning and developing urban spaces. The solutions to establishing inclusive urban public spaces that are accessible and safe for everyone in the community include good design and community dialogue. According to the research evidence, professionals in the built environment must be gender conscious when designing and creating urban spaces. Warwick Market, a public urban location in Durban, South Africa, was chosen for the study.